EKSPLORASI KAPABILITAS ODOO ERP MODUL HR DALAM MENDUKUNG OPERASIONAL SUMBER DAYA MANUSIA DI BANK ACEH SYARIAH - M.Rifqi Ghifari; Nur Wijayaning Rahayu (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
In the digital era, the banking industry requires integrated information systems to maintain operational efficiency. This study aims to explore the capabilities of the Odoo ERP HR module in supporting personnel operations at Bank Aceh Syariah, which currently faces challenges such as manual processes, data redundancy, and technical